BOSQUE THROWERS SPORT MANY YEARS OF WORK PROCEDURE FOR PLANNING. (On the example of athletes aged 14-16) - I.E.Rozmatov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the organization of the training process, the correct solution of the tasks set during the training. When writing the work, it was noted the correct distribution of the duration of training and competitions according to the annual plan, as well as the orderly performance of physical exercises with strength.